Indictment of Child Labor by the Arts - Department of Film, Television and Theatre (2013)
Indictment of Child Labor by the Arts February 24-26, 2013 Carlos Arejola National Commission for Culture and the Arts, Manila Terrence Coonan Center for Advancement of Human Rights, Florida State University Anton Juan Department of Film, Television and Theatre, University of Notre Dame Paolo Carozza The Center for Civil and Human Rights Notre Dame Law Schoolhttps://scholarship.law.nd.edu/ndls_posters/1072/thumbnail.jp